Locuciones latinas y variación lingüística en el español del siglo XXI - López González, Antonio María (Collectanea Philologica, 2024)
The objective of this article is to analyze the effect of linguistic variation in Latin idioms in Spanish, invariable lexical units, from a normative point of view. To do this, first of all, we define and distinguish Latin idioms within Latinisms in the Spanish language. Afterwards, we present its typology and main structures, according to Sánchez Martínez (1993). Later we discuss the normative treatment of Latin phrases by RAE, not exempt from some contradictions and changes in criteria over time. In the analytical part, we synthesize the meaning and normative use of 32 widely used Latin idioms. Finally, based on the linguistic corpus CORPES XXI, we carry out a quantitative analysis of the linguistic variants of the selected Latin idioms, with an example of each variant.